Two Policy Approaches to Native Education: Can Reform Be Legislated? - Brady, Patrick (Canadian Journal of Education/Revue canadienne de l'éducation, 1995)
The evolution of Canadian federal policy for Native elementary and secondary education has followed a pattern remarkably similar to that in the United States. A significant difference in the provision of educational services to indigenous peoples is, however, that whereas the United States has historically attempted to regulate and reform Native education through federal legislation, Canada has generally eschewed such a proactive strategy in favour of what Hall (1992) refers to as the “No Policy-Policy.” In this article I examine the evolution of Native education policy in both countries to determine which approach has brought Native people closer to their desired goal of having control over their children’s education. La politique fédérale canadienne d’enseignement primaire et secondaire destinée aux autochtones suit une évolution semblable à celle des États-Unis. ll existe toutefois une différence significative dans la prestation des services éducatifs aux peuples autochtones: les États-Unis ont toujours tenté de réglementer et de réformer l’éducation des autoch- tones par le biais de lois fédérales tandis que le Canada évite, en règle générale, ce genre de stratégie proactive et préfère ce que Hall (1992) désigne comme une “politique de non-politique.” Dans cet article, l’auteur analyse l’évolution, dans les deux pays, de la politique en matière d’enseignement aux autochtones afin de déterminer quelle approche permet aux peuples autochtones de se rapprocher de leur objectif, qui est de contrôler l’éducation de leurs enfants.